2017
DOI: 10.1002/capr.12135
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of psychotherapists’ experiences in medically driven cancer care settings

Abstract: Aim This study explored psychotherapists’ experiences of medical language used in cancer care settings and the implications for counselling clients in medically driven cancer settings. Method Semi‐structured interviews were conducted with five psychotherapists. Data were collected using Interpretative Phenomenological Analysis (IPA). Findings Participants found medical language difficult to understand when communicating with health professionals within multidisciplinary teams (MDT). They also considered focusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The current study also revealed that an approach to health care embedded in the medical model often affects communication between the therapists and other health professionals and between clinicians and patients. Issues arising from power dynamics experienced by psychotherapists in medically driven oncology settings were discussed in previous research (Reitano, 2017). The current study contributed to the finding that working within a medical model often encouraged unhealthy competition and unconstructive criticism within oncology teams and therefore led to tension, miscommunication, increased occupational stress and a lack of team cohesion.…”
Section: Discussionmentioning
confidence: 99%
“…The current study also revealed that an approach to health care embedded in the medical model often affects communication between the therapists and other health professionals and between clinicians and patients. Issues arising from power dynamics experienced by psychotherapists in medically driven oncology settings were discussed in previous research (Reitano, 2017). The current study contributed to the finding that working within a medical model often encouraged unhealthy competition and unconstructive criticism within oncology teams and therefore led to tension, miscommunication, increased occupational stress and a lack of team cohesion.…”
Section: Discussionmentioning
confidence: 99%